Peluang dan Tantangan Pengembangan Usahatani Tomat dan Pengaruhnya Terhadap Pendapatan Petani di Kecamatan Ruteng Kabupaten Manggarai - Jandu, Inosensius Harmin; Santu, Loerensius; Sudirman, Paulus Every (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Agriculture is a sector that has an important role in the economy in Indonesia. One agricultural commodity that has great potential is horticulture. Horticulture is one of the agricultural subsectors that has the potential to make a major contribution to economic development and plays an important role in the source of farmers' income, trade and employment. This research aims to determine the opportunities and challenges of developing tomato farming and its impact on farmers' income in Ruteng District, Manggarai Regency. The research was conducted in Ruteng District, Manggarai Regency with the consideration that this area is one of the areas for developing tomato horticulture farming. Data collection was carried out by interviewing main and key informants consisting of farmers, heads of farmer groups, agricultural extension workers. Data sources consist of primary data and secondary data. Research result. By taking advantage of supportive climate conditions, optimizing high market demand, managing stable selling prices, and diversifying products, farmers in Ruteng District have a good opportunity to develop tomato farming in a sustainable manner and can improve their standard of living. In facing farming challenges, it is important to have a holistic and integrated approach between governments. in terms of providing technological support, education, access to capital and risk management to help increase productivity, sustainability and income of farmers in Ruteng District. Apart from that, intense assistance to farmers in implementing good agricultural practices will also support increasing crop yields and farmer welfare. With the implementation of the right strategy and continuous support, tomato farming in Ruteng District has great potential to increase productivity, farmer income and contribution to the local economy.